Effect of splenectomy and ligature of the left gastric vein on portal hypertensive colopathy in carriers of surgical hepatosplenic schistosomiasis mansoni - Justo,Claudia Rosalí Esmeraldo (2005)
PURPOSE: Esophageal variceal sclerotherapy and band ligation seem not to affect the endoscopic findings of Portal Hypertensive Colopathy (PHC) of cirrhotic patients. The aim was to assess the effect of splenectomy and ligature of the left gastric vein on the PHC in carriers of hepatosplenic schistosomiasis mansoni who underwent this surgery when they were between 9 and 18 year-old. METHODS: Fourteen patients, mean age of 19.1±3.1 years, were included in the postoperative group (GI). The follow-up was from 1 to 9 years. The preoperative group (GII) consisted of nine patients, mean age of 14.0 ± 3.1 years. Full-length colonoscopy was carried out in all patients. Search was made for PHC lesions. RESULTS: Telangiectasy (GI 100% vs GII 100%), increased vascularisation (GI 57.1% vs GII 100%), focal and diffuse hyperemia (GI 14.3% vs GII 66.7%), angiodysplasia (GI 7.1% vs GII 33.3%), and rectal varix (GI 0% vs GII 55.6%) were the most frequent findings. It was observed that the patients of this series tended to exhibit fewer hemodynamic manifestations of the PHC after treatment (postoperative versus preoperative - chi2 = 8.155 p = 0.004). CONCLUSION: Splenectomy and ligature of the left gastric vein tend to reduce the abnormal vascular findings of PHC in carriers of hepatosplenic schistosomiasis mansoni.